Exploring Sociopolitical and Religious Meanings from a BBC News on a Terror Attack: A Functional Linguistic Analysis. - Rahaman, Sohanur (Advances in Social Sciences Research Journal, 2021)
This study is a functional grammatical analysis of BBC news on a New York attack where eight were killed by a man driving a truck by the application of Halliday’s Systematic Functional Grammar (SFG). By analysing the systems of grammar at the clause level, I show that the text at the discourse level makes different meaning across the news. Sayfullo Saipov, an immigrant who came to the US in 2010, has developed negative actions such as killing eight people, hurting 11, aiming at innocents, striking cyclists, hitting a school bus, injuring adults and children, and in all of his actions eventually “the innocent” are affected as a goal. Another significant goal i.e. “note” was found which shows his cohesion with the so-called Islamic States. Nevertheless, they are using the name of “Islam” but they don’t know or they don’t follow the script of Islam or at least the basics of Islam, it proven by the killer are all actions because according to The Holy Quran” killing a single innocent is even strongly prohibited in Islam, it is like killing the whole humanity. Identifying and attributing processes have identified here “The attack” as a “terrible” incident which is done by the attacker and attributing processes ascribe “bad qualities” of carriers (the attacker). The Killer is the highest number of “Actor” in terms of the transitivity process, which means he is in a “destructive power”. The police are the second-highest “actor” who performs some physical actions such as shooting the driver, arresting the driver, taking the attacker to hospital. The situation was going to get ugly by the killer’s actions and for this reason; the police accomplish these professional actions to make meaning of “safety of innocent”. The killer is a “single” person but his negative actions convulsed the whole city even whole country, and all big names like President, City mayor, police commissioner immediately were made get involved into “verbal actions” interfering, and reacting, saying, commenting etc. Thus the study frets out some significant meaning through grammar choices in the news genre in question.